1994
DOI: 10.1002/chin.199411329
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: 2‐Styrylchromones: Biological Action, Synthesis, and Reactivity

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…( E )‐2‐Styrylchromones were synthesised by a three‐step sequence starting from 2'‐hydroxyacetophenone and the appropriate cinnamoyl chloride, commercially available in the case of 1 or prepared in situ from cinnamic acids and phosphoryl chloride for 1a–c [9c]. The 12 H ‐benzo[12 a ]xanthen‐12‐one 21 was prepared according to a literature procedure involving the irradiation of ( E )‐2‐styryl‐4 H ‐chromen‐4‐one ( 1 ) with a high‐pressure Hg lamp at room temperature .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…( E )‐2‐Styrylchromones were synthesised by a three‐step sequence starting from 2'‐hydroxyacetophenone and the appropriate cinnamoyl chloride, commercially available in the case of 1 or prepared in situ from cinnamic acids and phosphoryl chloride for 1a–c [9c]. The 12 H ‐benzo[12 a ]xanthen‐12‐one 21 was prepared according to a literature procedure involving the irradiation of ( E )‐2‐styryl‐4 H ‐chromen‐4‐one ( 1 ) with a high‐pressure Hg lamp at room temperature .…”
Section: Methodsmentioning
confidence: 99%
“…They are known to present anti‐allergic, antitumor,[1b,4] antiviral, anti‐oxidant, and anti‐inflammatory properties and also for their use as antagonists of A 3 adenosine receptor . In view of the important biological activities described in the literature for this family of compounds, 2‐styrylchromones represent a rather important substrate and have been used in numerous transformations …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent theoretical study [34], a correlation was found between the lipoxygenase inhibitory activity of flavonoid molecules and their planar character, which probably facilitates the access, through a hydrophobic cavity, to the catalytic site of the enzyme. Considering this rationale, the planar character of 2-SC [16,29,35], conferred by the styryl link between the B-ring and the C-ring, may contribute to their effectiveness as 5-LOX inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…The first step involves the O-acylation of appropriate 2 0 -hydroxyacetophenones with cinnamoyl chloride derivatives to give 2 0 -cinnamoyloxyacetophenones. These intermediates were converted into 5-aryl-3-hydroxy-1-(2-hydroxyaryl)-2,4-pentadien-1-ones by the base-catalysed Baker-Venkataraman rearran- gement [27][28][29]. The cyclodehydration of these b-diketones with a mixture of DMSO and a catalytic amount of iodine or ptoluenesulfonic acid gives polybenzyloxy-2-SC, which were debenzylated by treatment with hydrogen bromide in acetic acid at reflux, to give the expected hydroxy-2-SC 1A-1D, 2A-2D and 3A-3D.…”
Section: Reagentsmentioning
confidence: 99%